Plasticity of ventral tegmental area disturbance during abstinence after repeated amphetamine exposure: restoration by selective activation of group II metabotropic glutamate receptors - Valenti, Ornella; Rekawek, Katarzyna Anna; Wieser, Sophie; Bulut, Hilal; Scholze, Petra; Boehm, Stefan (Frontiers in Pharmacology, 2025)
Background and aimsThe psychostimulant actions of amphetamine (AMPH) have been correlated with its ability to orchestrate ventral tegmental area (VTA) dopamine (DA) neuron activity states and, thus, DA release in output regions: in rats, a single exposure is sufficient to reduce the fraction of spontaneously active DA neurons, i.e., DA neuron population activity, whereas AMPH abstinence after repeated exposure leads to an increase. Here, this switch in DA neuron activity was resolved in detail in mice, and its sensitivity towards activation of group II metabotropic glutamate receptor (mGluR2 and mGluR3) was investigated.Experimental procedureAll experiments were conducted on C57BL/6J male mice. After repeated AMPH administration (2 mg/kg), the amine was withdrawn for up to 15 days and VTA DA neuron activity was assessed. The involvement VTA afferent regions with respect to AMPH actions was analyzed either by local instillation of drugs or through inactivation by tetrodotoxin. Selective agonists or allosteric modulators of mGluR2 and mGluR3 were used to explore whether group II mGluR might interfere with VTA disturbances caused by the amine.ResultsAfter repeated AMPH exposure, VTA DA neuron activity remained reduced for 4 days and then rose to a hyperdopaminergic state within 15 days. The initial hypodopaminergia was coordinated by an amygdala (AMG) - nucleus accumbens (NAc) -VTA pathway, whereas the hyperactivity relied on ventral hippocampus (vHPC). Hypodopaminergic VTA activity was recovered towards physiological levels by activation of mGluR2, but not mGluR3, and this remission was contingent on glutamatergic transmission within NAc and propagation via the ventral pallidum. Results of a light-dark transition task confirmed anxiolytic efficaciousness of mGluR2 activation. The hyperdopaminergic VTA activity, in contrast, was normalized by selective activation of mGluR3, but not mGluR2, within vHPC. AMPH re-exposure after abstinence turned VTA activity down, but this suppression involved alternative circuits and could no longer be rescued by mGluR activation.ConclusionThus, abstinence from repeated AMPH intake drives VTA activity from hypo-into hyperdopaminergic states, and both can be readjusted towards physiological levels via different members of group II mGluRs.